2012
DOI: 10.1016/j.bbr.2011.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gonadectomy on sex- and age-typical responses to novelty and ethanol-induced social inhibition in adult male and female Sprague-Dawley rats

Abstract: Sex- and age-typical responses to ethanol and novel stimuli tend to emerge postpubertally, suggesting a potential organizational or activational role for pubertal hormones in these behaviors. To test this possibility, male and female rats were gonadectomized (GX) or received sham gonadectomy (SH) either prepubertally on postnatal day (P) 23 (early) or in adulthood on P70 (late). Animals were tested as adults for response to novelty and, on the following day, challenged with either saline or ethanol (1g/kg) pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 55 publications
5
40
3
Order By: Relevance
“…Work using this approach has found that animals that do not experience normal developmental increases in pubertal hormones exhibit deficits in later expression of a variety of reproductive behaviors and other adult-typical, sexually dimorphic behaviors (see Sisk & Zehr, 2005, for review). In contrast, we have found pubertal hormones to exert surprisingly modest influences on alcohol intake and sensitivity (Vetter-O’Hagen & Spear, 2011, 2012). For instance, gonadectomy in males (but not females) either prepubertally or in adulthood increased alcohol intake in adulthood, an increase largely reversed by testosterone replacement (Vetter-O’Hagen & Spear, 2011; Vetter-O’Hagen, Sanders & Spear, 2012); this pattern of findings is consistent with an activational role of testosterone in adulthood rather than pubertally-related processes.…”
Section: Contributors To Adolescent-typical Alcohol Sensitivitiescontrasting
confidence: 65%
See 2 more Smart Citations
“…Work using this approach has found that animals that do not experience normal developmental increases in pubertal hormones exhibit deficits in later expression of a variety of reproductive behaviors and other adult-typical, sexually dimorphic behaviors (see Sisk & Zehr, 2005, for review). In contrast, we have found pubertal hormones to exert surprisingly modest influences on alcohol intake and sensitivity (Vetter-O’Hagen & Spear, 2011, 2012). For instance, gonadectomy in males (but not females) either prepubertally or in adulthood increased alcohol intake in adulthood, an increase largely reversed by testosterone replacement (Vetter-O’Hagen & Spear, 2011; Vetter-O’Hagen, Sanders & Spear, 2012); this pattern of findings is consistent with an activational role of testosterone in adulthood rather than pubertally-related processes.…”
Section: Contributors To Adolescent-typical Alcohol Sensitivitiescontrasting
confidence: 65%
“…In contrast, we have found pubertal hormones to exert surprisingly modest influences on alcohol intake and sensitivity (Vetter-O’Hagen & Spear, 2011, 2012). For instance, gonadectomy in males (but not females) either prepubertally or in adulthood increased alcohol intake in adulthood, an increase largely reversed by testosterone replacement (Vetter-O’Hagen & Spear, 2011; Vetter-O’Hagen, Sanders & Spear, 2012); this pattern of findings is consistent with an activational role of testosterone in adulthood rather than pubertally-related processes. Moreover, neither pre-pubertal or adult gonadectomy altered sensitivity to alcohol’s social inhibitory effects, although the microstructure of social behavior was affected in both males and females (Vetter-O’Hagen & Spear, 2012).…”
Section: Contributors To Adolescent-typical Alcohol Sensitivitiescontrasting
confidence: 65%
See 1 more Smart Citation
“…We did not monitor the estrous cycle in alcohol or sucrose responding females. There is evidence in support of [44] and against [4547] the influence of ovarian hormones on alcohol self-administration. Previous work using Sprague-Dawley females showed no effect of the estrous cycle on alcohol responding under an FR1 schedule [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this study, CTA to a range of ethanol doses was assessed across a broad age range-- at ages chosen to represent pre-adolescents/juveniles (P23-2 5 ), early (P28-30), mid (P35-3 7 ), and late (P42-44) adolescents, “emerging adults” (P52-54), and adults (P72-74), based on prior literature showing discrete developmental windows within adolescence (e.g. Vetter-O’Hagen et al, 2012; Spear, 2015). Both males (Experiments 1 and 2a) and females (Experiment 2b) were examined.…”
Section: Introductionmentioning
confidence: 99%